Peran Mahkamah Konstitusi dalam Penegakan Hukum Tatanegara di Indonesia: Studi Kasus Putusan-Putusan Penting - Harlina Hamid (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This article discusses the role of the Constitutional Court (MK) in enforcing constitutional law in Indonesia, which is the highest judicial institution in supervising and enforcing the constitution. In this context, this study focuses on the analysis of several important decisions taken by the MK, which not only affect legal aspects, but also have significant social and political impacts. Through a qualitative descriptive approach, this article identifies and evaluates crucial decisions, such as decisions related to general elections, human rights, and democratic principles. This study aims to understand how these decisions contribute to shaping legal norms and addressing various challenges in Indonesian constitutional law. Furthermore, this article also explores the implications of these decisions for society, including their influence on public trust in legal institutions and political participation. Thus, this study seeks to provide a comprehensive picture of the position of the MK as the vanguard in enforcing constitutional law, as well as the challenges it faces in carrying out its functions and responsibilities. The results of this analysis are expected to provide readers with insight into the importance of the MK's role in maintaining the constitution and encouraging better legal reform in Indonesia, as well as providing recommendations for improving the performance and transparency of this institution in the future.